(untitled) (Journal of Pathology of Nepal, 2020)
Malignant odontogenic tumors are rare and represent approximately 1% of all oral malignancies. Ameloblastic Carcinoma is an uncommon malignant odontogenic tumor accounting for 1.5%-2.0% of all odontogenic tumors that can be difficult to differentiate from Ameloblastoma, and can arise directly as an undifferentiated lesion or from a preexisting benign lesion. It is a highly aggressive tumor with rapid growth and a high potential for distant metastasis. The most common site of occurrence is posterior mandible. Here we present a case report of Ameloblastic Carcinoma, relapse case of a benign lesion 15 years after surgery which presented as firm growth in the right mandible for 2 months.